Education On Breast Self Examination (SADARI) as Early Detection of Breast Cancer in Adolescent Girls at SMP Negeri 3 Lubuk Pakam - Hariati, Mayang Citra; Cahya, Rani (JURNAL PENGMAS KESTRA (JPK), 2025)
Breast cancer (Ca Mammae) is a group of abnormal cells in the breast that continue to multiply, forming a lump in the breast. The body contains millions of cells. One of them is the abnormal cell or metaplastic cell, which is a cell that can change but is still within normal limits. Breast cancer is not a very frightening specter for all women, including teenagers. One way to detect breast cancer is through self-breast examination, SADARI, which is an examination of one's own breast to find lumps that may be present. This community service activity is conducted through a series of lectures and demonstrations using educational media in the form of materials, educational videos, and direct demonstrations to students, followed by a question-and-answer session and a redemonstration for participants on self-breast examination (SADARI). This activity was held on May 22, 2025, and was attended by 26 female students of SMP Negeri Lubuk Pakam. The activity lasted for 1 hour and 30 minutes. This educational event emphasized the importance of self-breast examination and how to perform it. As a result of this activity, the female students of SMP Negeri 3 Lubuk Pakam have a good understanding of self-breast examination and how to perform the examination correctly. The conclusion of this activity is that all female students are also committed to routinely performing self-breast examinations (SADARI) and to support the continuity of information and education, there needs to be ongoing guidance and also promotional and educational actions so that all women can live healthily if abnormalities in the breasts are detected earlier.